Storyworlds: the shark with no teeth - Rayner, Shoo (Heinemann UK, 2000)
*The Shark with No Teeth* is a charming children$1 (Bs book about a shark named Finn who is sad because he has lost all his teeth. As Finn tries to find a way to regain his teeth, he discovers that he doesn$1 (Bt need them to be fierce or powerful. The story teaches young readers about self-acceptance, resilience, and that being kind and confident is more important than appearances.s